Collaborative governance: Analysis of active transparency in public health consortia in the state of Ceará / Brazil - de Oliveira, Antonio Rafael Valério (2024)
Inter-municipal public consortia enable collaboration between municipalities and states, and it is urgent that their collaborative governance structure fosters access to information and promotes transparency. The general objective was to verify the level of transparency of the health consortia in Ceará, accompanied by the elaboration of a ranking of the most transparent. The methodology encompasses quantitative approaches, characterized as descriptive research. Data collection took place on the websites of the 21 intermunicipal consortia, identified using the Database of the National Confederation of Municipalities. A general analysis of the characteristics of the consortia, the descriptive analysis of the variables, cluster analysis and ranking organization were performed. The results reveal an incomplete disclosure, with an average of 9.6, indicating deficiencies in fiscal transparency, especially related to the Fiscal Management Report (RGF) and the Summary Report on Budget Execution (RREO). Despite satisfactory real-time disclosure, overall transparency averages 75%, necessitating improvements in the implementation of answers to frequently asked questions. Most of the consortia have low average transparency, and none meets all the criteria, with CPSMCAM, CPSMI and CPSRCAS standing out as the most transparent. The results show that the health consortia in Ceará do not fully disclose all the criteria analyzed, revealing a low transparency, especially in relation to financial data such as budget and financial statements. The research contributes to the literature by highlighting the importance of transparency for the improvement of public services, introducing the disclosure index of public consortia as a relevant metric in this context.